Posterior tibial tendon dysfunction alters the midfoot mechanics and energetics during gait. Issue 9 (26th December 2021) - Wuite, Sander; Deschamps, Kevin; Eerdekens, Maarten; Scheys, Lennart; Loomans, Laura; A. Matricali, Giovanni
Abstract: A comprehensive insight into the in vivo foot kinetics of patients with posterior tibial tendon dysfunction (PTTD) is lacking to support clinical decision making. Our goal was to study how PTTD alters the kinetic and kinematic characteristics of the foot and ankle with a special focus on the midfoot joints. Multisegment foot joint kinetics and kinematics were compared based on the Rizzoli Foot Model and inversed dynamics between a control group ( n  = 25), patients with PTTD Stage II ( n  = 21) and PTTD Stage III ( n  = 4) over the entire stance phase. Compared to controls, a mean decrease in power generation of 1.3 W/kg was found in the Ankle joint in PTTD II patients ( p  < 0.001) and PTTD III patients of 1.5 W/kg ( p  < 0.001). In the Chopart joint, there was a mean increase in power absorption of 0.4 W/kg in the PTTD III patients ( p  = 0.014) and a mean decrease in power generation of 0.6 W/kg ( p  < 0.001) in the PTTD II patients. The distribution of total negative work showed a shift from the Ankle and first metatarsal phalangeal joint towards the Chopart joint in both PTTD compared with the control subjects. A significant reduction in range of motion was observed among both PTTD groups. The outcome of this study will enable the possibility to customize the conservative and surgical treatment of each patient with PTTD, to improve or even restore the kinetic features. This will prevent the natural deterioration of function seen in this pathology.